(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nowadays, many modern websites offer a variety of information services, providing a dynamically generated content for the end user. However, the more users are trying to obtain such content, the slower becomes its loading time in their browsers. This article explains the mentioned problem in detail, as well as examines the roots of this problem.